Elevated Red Blood Cell Distribution Width as a Poor Prognostic Factor in Patients With Hematopoietic Stem Cell Transplantation - Jia, Xiaojiong; Cheng, Si; Zhang, Long; Zheng, Yuan; Zou, Hua; Huang, Shifeng; Wang, Hongxu; Lu, Juan; Tang, Dijiao (Frontiers in Oncology, 2021)
Red cell distribution width (RDW), a measure of erythrocyte size variability, has been recently reported as an effective prognostic factor in critical illness. Hematopoietic stem cell transplantation (HSCT) has become the first choice of most patients with hematological malignancies. The aim of this study was to assess the changes RDW in patients with HSCT and analyze the relationship between RDW and HSCT. In this study, we retrospectively enrolled 114 hematopoietic stem cell transplant patients during the period from 2015 to 2019. Logistic regression and Kaplan Meier survival analysis were used for retrospective analysis. Multivariate analysis suggested that patients with elevated RDW (>14.5%) at three months post-transplantation has a poor clinical outcome compared with those with normal RDW≤14.5% (odds ratio [OR] 5.12; P = 0.002). Kaplan Meier method analysis demonstrated elevated RDW levels (>14.5%) after hematopoietic stem cell transplantation experienced shorter progression-free survival compared to those with normal RDW levels (P = 0.008). Our study demonstrated that RDW could be an easily available and potential predictive biomarker for risk stratification in patients with HSCT. Further prospective studies are determined to confirm the prognostic value of RDW in HSCT patients.